Pengaruh Seminar dan Diskusi Interaktif tentang Komitmen Organisasi terhadap Perilaku Lulusan dalam Meningkatkan Kinerja di Akademi Kesehatan John Paul II Pekanbaru - Maria, Anna (Civiliza Publishing, 2024)
The absorption and performance of graduates are part of the outcomes that must be achieved by every college, including Akademi Kesehatan John Paul II Pekanbaru (AKJP II Pekanbaru). Users of graduates hope to get workers who have insight, skills, and work behavior that can adapt to the vision, mission, and goals of the organization. Therefore, Akademi Kesehatan John Paul II Pekanbaru carries out activities to make graduates ready to work apart from trying to achieve the target of competent students in the national competency test to graduate on time. Because of that, AKJP II Pekanbaru held an interactive seminar and discussion activity